Electro‐optical spiking neural networks using an enhanced optical axon with pulse amplitude modulation and automatic gain controller - George‐Iulian Uleru; Mircea Hulea; Othman Isam Younus; Zabih Ghassemlooy; Sujan Rajbhandari (IET Optoelectronics, 2023)
Abstract Visible light communication can be leveraged to establish a wireless link between neurons in spiking networks even when neural areas are in relative motions. In electro‐optical spiking neural networks (SNN), parallel transmission is often achieved through wavelength division multiplexing (WDM). However, WDM can be prohibitive in certain applications due to the need for multiple narrow‐band transmitters and receivers with optical bandpass filters. Instead of WDM, an alternative approach of using non‐orthogonal multiple access is explored (NOMA) with a pulse amplitude modulation (PAM) scheme in optical axons to enable parallel neural paths in an SNN. To evaluate NOMA with PAM, the authors implement an electro‐optical SNN that controls the force of two anthropomorphic fingers actuated by the shape memory alloy‐based actuators. An optical reference channel is used to dynamically adjust the optical receiver's gain to improve the receiver's decoding performance. Experimental results demonstrate that the electro‐optical SNN can maintain control over the fingers and hold an object under varying channel conditions. Hence, the proposed system offers robustness against dynamic optical channels induced by the relative motion of neurons.